Defending the West : the Truman-Churchill correspondence, 1945-1960 - Truman, Harry S., 1884-1972 (Contributions to the study of world history, 2004)
Covers the wartime correspondence between President Truman and Prime Minister Churchill and includes more than a decade of subsequent personal and official correspondence between the two.